RESIDU LOGAM BERAT IKAN DARI PERAIRAN TERCEMAR DI PANTAI UTARA JAWA TENGAH (Residual Heavy Metals in Fish from Contaminated Water in North Coast of Central Java) - Agus Suyanto; Sri Kusmiyati; Chistina Retnaningsih (Universitas Muhammadiyah Semarang, 2010)
Heavy metal pollution is increasing in line with increasing industrialization. Research on the Heavy Metal Residues in fish from polluted water and unpolluted water in Central Java using descriptive-explorative research approach, using samples of fish from ponds and estuaries . Samples were taken from three locations coastal areas in district of Semarang, Tegal and Pati. Analysis of heavy metals consists of Pb, Cu, Zn, Hg, Cd, and As by AAS (Atomic Absorption Spectroscopy). The results showed levels of heavy metals from 0.08 to 0.12 ppm Hg above the threshold regulation Ditjen POM RI no 03725/B/SK/VII/89 on fish from polluted and unpolluted ponds and estuaries polluted and not polluted in Pati and Semarang. Zinc (Zn) heavy metal at 40.11 ppm from unpolluted estuaries district of Tegal above the set threshold. Key words: fish, ponds, esturia, contaminated heavy metals